Biomarkers Associated with Vascular Calcification in Peritoneal Dialysis. Issue 3 (May 2016) - Ramirez-Sandoval, Juan C.; Casanova, Ivan; Villar, Alejandro; Gomez, F. Enrique; Cruz, Cristino; Correa-Rotter, Ricardo
Background: Vascular calcification is strongly associated with cardiovascular disease and mortality. However, some factors related to vascular calcification in patients with end-stage renal disease receiving peritoneal dialysis (PD) remain unknown. This study aimed to evaluate the associations of osteoprotegerin (OPG), osteopontin (OPN), osteocalcin (OCN), fibroblast growth factor 23 (FGF-23), magnesium, and phosphate clearance with vascular calcification in PD subjects, assessed by plain radiographs. Methods: Simple vascular calcification scores (SVCS) obtained from plain X-rays of the pelvis and hands, and the Kauppila Index (KI) from lateral lumbar X-rays were assessed in 76 adults receiving PD for ≥ 6 months (43 women, median age 39 years, median time on PD 1.4 years). Levels of OPG, OPN, OCN, and FGF-23 were determined by luminometry. Results: Serum OPG levels were higher in subjects with vascular calcification ( n = 22 with SVCS > 3; n = 19 with KI > 7) compared with those with less calcification ( p < 0.001). Spearman's correlation coefficients between OPG and SVCS and KI were r = 0.49 and r = 0.51, respectively (both p < 0.001). Subjects with vascular calcification had significantly lower renal phosphate clearance. Multiple regression analysis showed that vascular calcification assessed by SVCS was associated with age ( r = 0.2, p = 0.042), diabetes mellitus ( r = 2.4, p < 0.001), body mass index (BMI) ( r = 0.09, p = 0.037), and OPG ( r = 0.22, p = 0.001). Vascular calcification assessed by KI was associated with age ( r = 0.16, p < 0.001), time on PD ( r = 0.54, p = 0.001) and OPG ( r = 0.08, p = 0.04). Osteocalcin, OPN, FGF-23, and magnesium were not associated with vascular calcification. Conclusions: Higher levels of OPG were consistently associated with vascular calcification in subjects on PD.